Analisis Potensi Bahaya Menggunakan Hazard Identification and Risk Assesment & Risk Control (HIRARC) (Studi Kasus : CV. Nadha Furniture) - Hadi, Khairul; Irawan, Risnadi; Akmal, Abdiel Khaleil; Ridha, Arrazy Elba; Fatah, Samsul; Kamal, Mustafa (Universitas Teuku Umar, 2024)
CV Nadha Furniture is a business entity operating in the furniture sector which produces various types of processed wooden goods that have sales value such as doors, frames and windows. The aim of this research is to identify potential hazards at each step of the work and carry out risk assessments, prevention and control of potential hazards found in the production process. The method used in this research is Hazard Identification and Risk Assessment & Risk Control (HIRARC). Based on the results of identifying potential hazards at CV Nadha Furniture, it has 5 potential hazards in the high category and 4 potential hazards in the medium category in the production process, including the raw material selection station has 1 potential hazard in the high category, the raw material cutting station has 2 potential hazard categories. high and 1 potential hazard in the medium category, the pattern forming station has 2 potential hazards in the high category and 1 potential hazard in the medium category, and the vinyl installation station and final checking and packaging stations have 2 potential hazards in the medium category. To minimize the level of risk from potential dangers, risk control is carried out which can be done by using gloves, safety helmets, masks and safety shoes as well as providing job training and conducting safety talks before carrying out work..